I’jāz Al-Qur’ān: Menelusuri Bukti Keotentikan Al-Qur’an - Sulaiman Ibrahim (Farabi, 2015)
Koran presented a challenge to everyone who doubted it to create something like the Koran. This challenge applies without any time limit. Therefore, the miracle of the Qur'an valid today. This article reinforces the argument that one of the authenticity of the Koran is the Koran's ability to survive throughout the centuries without any editorial changes even one letter. Metaphysical assurances given by God proved because until now no one was able to disrupt the contents of the Koran by changing the wording. Instead of editorial changes, changes in vowel or the letter will soon be known because so many Muslims in this world for generations who memorized the Koran. Moreover, with the printing and computerized systems today will further ensure the integrity and preservation of the Koran.